2018
DOI: 10.1371/journal.pone.0195479
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial-layer free transfer of mammalian cells using near infrared femtosecond laser pulses

Abstract: Laser-induced cell transfer has been developed in recent years for the flexible and gentle printing of cells. Because of the high transfer rates and the superior cell survival rates, this technique has great potential for tissue engineering applications. However, the fact that material from an inorganic sacrificial layer, which is required for laser energy absorption, is usually transferred to the printed target structure, constitutes a major drawback of laser based cell printing. Therefore alternative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…Our approach avoids these shortcomings by using fs NIR laser pulses in the biological optical window, which do not require inorganic sacrificial layers and do not induce DNA double strand breaks. [ 33 ] Only in the laser focus, the photon density is sufficient to initiate nonlinear absorption and an optical breakdown. [ 44 ] Outside of the focus, where no multiphoton absorption occurs, the 1030 nm laser pulses hardly interact with the cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our approach avoids these shortcomings by using fs NIR laser pulses in the biological optical window, which do not require inorganic sacrificial layers and do not induce DNA double strand breaks. [ 33 ] Only in the laser focus, the photon density is sufficient to initiate nonlinear absorption and an optical breakdown. [ 44 ] Outside of the focus, where no multiphoton absorption occurs, the 1030 nm laser pulses hardly interact with the cells.…”
Section: Resultsmentioning
confidence: 99%
“…This process can be used to transfer small gel‐droplets containing ≈10–30 cells to a target substrate with high cell viability. [ 33 ] Based on these findings, we have now elaborated a method, which allows the identification and selection of individual mammalian cells from a cell reservoir as well as the subsequent transfer of these cells to a target surface with single cell precision and a 93–99% cell‐survival rate, depending on cell type and target substrate (see Figure a,b). We have integrated this setup into an inverted optical microscope (Figure 1a), which allows us to use cell morphology (e.g., cell shape or size) or fluorescence to select and sort individual cells from a heterogeneous cell population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential niche market is the printing of biological materials, which are usually found in aqueous solutions and suspensions, and which are therefore transparent to most popular laser wavelengths. Thus, it has been proved that the technique is feasible for printing biomolecules like DNA and some proteins, and therefore for biosensor fabrication (Sections and ), and more recently it has been shown that FF‐LIFT is especially suited for printing living cells for tissue engineering applications (Section ). Another set of materials very attractive to be printed with the film‐free approach are optical grade adhesives, normally used in the fabrication of micro‐optical components …”
Section: Lift From Liquid Donor Filmsmentioning
confidence: 99%
“…This quest, to ultimately recreate the in vivo matrix in all its detail, continues to inspire new fabrication method developments. [15][16][17] Initially limited to 2D micro-patterning, such as elastomere stamps, [18,19] spotted DNA microarrays, [20] or polyacrylamide gels, [21] additive manufacturing increasingly expanded the capacity to engineer cell and tissue environments in vitro. [22] In particular, one-photon stereolithography and volumetric bioprinting achieved fast fabrication of clinically relevantly sized tissue constructs of protein-based resins at two-digit µm scale resolution.…”
Section: Introductionmentioning
confidence: 99%